OPTIMASI CAMPURAN AVICEL PH 101 DAN PATI JAGUNG DALAM PEMBUATAN TABLET EKSTRAK DAUN MIMBA (Azadirachta indica A. Juss) SECARA Simplex Lattice Design - Ilham Kuncahyo (Jurnal Farmasi Indonesia, 2009)
Avicel PH 101 is an excipient in tablet making that can be used as diluent, binder, lubricant, and disintegrator. Avicel is not economically an advantage so that it needs to be combined with cheaper materials. Combination of Avicel PH 101 with corn starch is able to accelerate the disintegration time of the tablet. Mimba (Azadirachta indica A. Juss) leave is a traditional medicine that is used as anti-inflammation. The study was to find out the optimum proportion of Avicel PH 101 and corn starch mixture in tablet making of mimba leaves extract by simplex lattice design method. The extract of mimba leaves was obtained by maceration of mimba leaves powder with ethanol 70%. The obtained extract was evaporated until a thick extract was obtained. Tablet formulation was based on SLD method with excipients of Avicel PH 101 (A) and corn starch (B) i.e. F1 (100% A), F2 ( 50% A : 50% B), F3 (100% B). The tablets of mimba leaves extract were made by wet granulation. The equation was used to make tablets with total respond of the most optimum granules physical properties. The data of the physical properties of granules from optimum formula as calculation result based on SLD equation with the experiment result was analyzed using T-test. Tablets from optimum formula were physically tested including weight uniformity, hardness, friability and disintegration time. The result of theexperiment indicated that the mixture of 90% Avicel PH 101 – 10% corn starch produced an optimum result in granules physical properties and the obtained tablets of mimba leaves extract fulfilled tablet physical property test.